Survival Strategy Through Segmenting, Targeting, Positioning Approach: A Study On Warung Lucau Angkringan in Facing Market Competition - Dynda Prista; Nur Afika Fitriani; Satrio Ahmadtul Firdaus Romadhoni; Nazwan Suharsono; Sudarmiatin Sudarmiatin (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the survival strategy applied by Warung Lucau Angkringan, a Micro, Small, and Medium Enterprise (MSME) in the culinary sector in Banyuwangi, in the face of increasing intensity of market competition. Carrying the concept of angkringan based on Osing local culture, Lucau Angkringan offers differentiation through signature dishes such as Sambal Lucau and Ayam Kesrut Lucau. However, limitations in marketing strategy, unclear market segmentation, and competition with large-scale restaurants are the main obstacles in developing its business. Through the Segmenting, Targeting, and Positioning (STP) approach, this research shows that Lucau Angkringan can identify and segment the market more effectively, and focus its marketing strategy on local consumers and tourists seeking authentic culinary experiences. In addition, innovations in digital marketing and efficient operational management are needed to improve competitiveness and expand market reach. The results of this study indicate that the proper implementation of STP strategies, accompanied by the optimization of digital marketing, can support the sustainability and growth of Warung Lucau Angkringan amidst the competitive culinary industry.